Autonomous detect and avoid algorithm respecting airborne right of way rules - Mukherjee, Anurag; Mondal, Sabyasachi; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Robust conflict resolution systems are crucial for BVLOS (beyond visual line of sight) operations of UAVs (Unmanned Aerial Vehicles) in the unsegregated airspace. The present conflict resolution research focus is skewed towards optimal path planning, often ignoring the airborne Right-of-way rules prescribed by the FAA and CAA. Although this approach might result in the most optimal path to resolve the conflict, it can cause confusion among other airspace users if the rules of the air are not obeyed when operating in the vicinity of other aircraft. In the present work, a real-time model predictive control approach is proposed that heavily prioritizes adherence to the prescribed right-of-way rules of the air. The maneuvering limitations of the involved aircraft are also taken into account. Several conflict scenarios were simulated, and the results show that the developed algorithm could resolve all conflicts.